Authorship and publication date of the Palaeozoic genera Cypridinella, Cypridellina, Sulcuna, Rhombina, and Offa (Ostracoda: Myodocopa) - Kornicker, Louis S. (Zootaxa, 2006)
Authorship and publication date of the Palaeozoic genera Cypridinella, Cypridellina, Rhombina, Sulcuna, and Offa have been attributed in the literature to either Jones 1873a, Jones & Kirkby, 1874, or Jones, Kirkby, and Brady, 1874, or 1884 (see Kornicker, 2001). Kornicker (2001) concluded that the correct authorship and publication date of the five genera are Jones, 1873a. Becker (2004) disputed this and argued that the correct authorship and publication date of the first four genera are Jones and Kirkby, 1874 (Offa not mentioned), centering his argument on the genus Sulcuna. On June 10, 2005, I forwarded a request to the International Commission on Zoological Nomenclature (ICZN) requesting a ruling on the identity of the author of the Palaeozoic genus Sulcuna. An answering letter received in August 2005 from the ICZN Secretariat (Fig. 1) stated that Jones (1873a) should be credited as the author of the genus Sulcuna.